A case of eperythrozoonosis in royal python (Python requis) in zoological garden in Ibadan, Nigeria (2010)
Eperythrozoonosis in Royal python reported. Clinical observations included dullness, paleness and jaundiced mucous membrane. Parasitological examination revealed rickettsiae, Eperythrozoon. Stressful condition associated with Royal python in captivity resulted in lower immunity and development of evident infection. Routine screening of Royal Python's prey to prevent transfer of ticks by contact is advocated.